Strategi Pembelajaran Pendidikan Agama Kristen oleh Guru di Tengah Pandemi Covid 19 - Masda Engkol; Daniel C. Kambey; Art Thomas (Peneliti.net, 2021)
The purpose of this research is to find out the learning strategy of Christian education in the midst of the covid-19 pandemic. This research uses qualitative approach by using data collection techniques, the instrument use for this research are as follow (1) Observation (2) Interview (3) Ducument study. In analyzing data, the researcher takes the steps of (1) data collection, (2) data categories, (3) data reduction, (4) data display, (5) drawing conclusion. Based on the result, shows that (1) Online learning is done with access to existing technology media such as googlemeet, zoom, google classroom, google form, and whatsapp groups (2) Christian education learning in the midst of the covid-19 pandemic did not run well and was less effective because there were obstacles experienced and could not control the children. Children’s learning activities at home really need parental attention, therefore parents must be sensitive to the child’s condition in the learning process so that when there is attention from parents, parents will direct and guide children in receiving material.